Pembinaan Gadis-Gadis Penghibur - Uras Siahaan; Agustina Evelin Tambunan (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2020)
Abstract: This paper is based on the experience of nurturing and educating from a social worker at the Berdikari Foundation (pseudonym) in South Jakarta, in collaboration with the Manunggal Foundation (pseudonym), to educate abandoned children, who plunge into the Night world, as aneffortto